PENGETAHUAN DAN SIKAP WANITA RAWAN SOSIAL EKONOMI (WRSE) TENTANG PENCEGAHAN PENANGGULANGAN HIV/AIDS DI KOTA PEKALONGAN TAHUN 2014 - Baroroh, Ida; Hidayati, Nur; Kusumawardani, Dian (BAPPEDA Kota Pekalongan, 2014)
Human Immunodeficiency Virus (HIV) is the virus that causes Acquired Immunodeficiency Syndrome (AIDS), which is a global health problem in both developed and developing countries. HIV / AIDS is a sexually transmitted disease that can be transmitted throughout society from infants to adults both male and female. Women's socio-economic prone included into the vulnerable groups because of poor health status, durability and family welfare would have the potential to perform high-risk of HIV infection and AIDS. The purpose of the research is to analyze the knowledge and attitudes of women's socio -economic prone on the prevention of transmission of HIV / AIDS in Pekalongan. This research method is quantitative and qualitative. The samples of this research are 47 WRSE in Pekalongan, taken 4 WRSE study subjects aged 18-50 years with criteria, are married and have children, widows live / dead widow who becomes the primary breadwinner families or married to a husband who worked at sea for long periods (return 3 months or more), working as a bus driver Inter-City Inter-Province (AKAP), truck drivers, or work outside the city without clarity, have dependents by more than 3 people, stay in Pekalongan. Collecting data through in-depth interviews and analysis with content-analysis. The results showed WRSE knowledge about STDs, HIV / AIDS as well as an overview of HIV disease AIDS is still very limited, limited knowledge society is due to the lack of dissemination to the public of information relating to HIV / AIDS and VCT clinics presence in Pekalongan by the Government. Negative attitudes towards PLHIV community committed (People Living with HIV / AIDS) is caused by ignorance of the community clearly. It is recommended to promote coordination among agencies in providing public education, socializa tion expanded, the type of information plus, especially socialization related to the prevention of disease transmission, forming an organization engaged in the protection and prevention of HIV/AIDS. Keywords: HIV / AIDS, WRSE, Knowledge, Attitude